2000
DOI: 10.1590/s1516-89132000000200001
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Ilex paraguariensis St. Hilaire, 1822 to Meloidogyne incognita and M. paranaensis and their influence on development of plantlets

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…A. pintoi did not allow the multiplication of M. incognita and M. mayaguensis, indicating the inability of A. pintoi to act as a host to these two root-knot nematodes. Santiago et al (2002) investigated the A. pintoi reaction to M. paranaensis and M. incognita races 1, 2, 3, and 4. They reported that no root penetration by M. incognita and M. paranaensis juveniles had occurred, and hence there was no gall or egg mass formation.…”
Section: Resultsmentioning
confidence: 99%
“…A. pintoi did not allow the multiplication of M. incognita and M. mayaguensis, indicating the inability of A. pintoi to act as a host to these two root-knot nematodes. Santiago et al (2002) investigated the A. pintoi reaction to M. paranaensis and M. incognita races 1, 2, 3, and 4. They reported that no root penetration by M. incognita and M. paranaensis juveniles had occurred, and hence there was no gall or egg mass formation.…”
Section: Resultsmentioning
confidence: 99%
“…Meloidogyne le confieren producir un innegable impacto negativo en los cultivos, y en lo que respecta a la yerba mate las investigaciones aún son insuficientes y desactualizadas, de esta forma, Lozano & Santos (1991) y Santiago et al (2000) se encuentran entre los pocos reportes disponibles y afirmaron que el nematodo de la agalla produjo daños y redujo el rendimiento del cultivo de yerba mate.…”
Section: Las Características Propias Del Endoparásitounclassified
“…M. paranaensis foi detectado também na Guatemala e Havaí -Estados Unidos (CARNEIRO et al, 2004). Sua hospedabilidade e reprodução foram relatadas em plantas de café -Coffea arabica L. (CARNEIRO et al, 1996), erva mate -Ilex paraguariensis L. (SANTIAGO et al, 2000), soja -Glycine max L. Merril (CASTRO et al, 2003b;ROESE et al, 2004;ROESE et al 2007), aveia preta -Avena strigosa e aveia branca -Avena sativa (MORITZ et al 2003a;CARNEIRO et al, 2006a), milho -Zea mays L. (MORITZ et al, 2003b;CARNEIRO et al, 2007), diversas plantas daninhas (ROESE; OLIVEIRA, 2004;MÔNACO et al, 2008), mandioca -Manihot esculenta L. (CARNEIRO et al, 2006b), sorgo -Sorghum bicolor (MORITZ et al, 2006), diversas gramíneas (CARNEIRO et al, 2006c), trigo -Triticum aestivum (SCHERER et al, 2006), híbridos de sorgo e cultivares de milheto (CARNEIRO et al, 2007) Reddy (1984) relatou os efeitos de M. incognita sobre o patchuli (Pogostemon cablin) mediante a inoculação de 100, 1000, 10000 ovos/J2 durante 180 dias. Houve uma redução nos pesos de parte área e raíz.…”
Section: Meloidogyne Paranaensis Carneiro Et Alunclassified